STUDI EMPIRIS TERHADAP RETURN ON ASSETS PADA PERUSAHAAN MANUFAKTUR PT. UNILEVER INDONESIA TBK PERIODE 2014-2023 - Septi Dwi Cahyani; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2025)
This study aims to empirically examine the effect of financial ratios on Return on Assets (ROA) in the manufacturing company PT Unilever Indonesia Tbk during the 2014-2023 period. The research method used is quantitative research with panel data collection from the company's financial statements for 2014-2023. Data analysis uses multiple linear regression analysis techniques to determine the effect of these variables simultaneously and partially on ROA. The results showed that partially Current Ratio had no significant effect on ROA with a T Count value of 0.847 < 2.447 with a significance level of 0.436 > 0.05. Debt to Equity Ratio produces a T Count value of -3.062> 2.447 with a significance value of 0.028 < 2.447 and a significance value of 0.690 > 0.05 indicating that Total Assets Turnover has no significant effect on ROA and Price to Book Value has no significant effect with a T Count value of 0.868 < 2.447 with a significance value of 0.425 > 0.05. Simultaneously, the variables Current Ratio, Debt to Equity Ratio, Total Assets Turnover and Price to Book Value together have a significant effect on ROA with a calculated F value of 30.385 exceeding the F table of 5.19. Then the coefficient of determination test results of 92.9% of the dependent variable Return on Assets is influenced by the independent variables Current Ratio, Debt to Equity Ratio, Total Assets Turnover and Price to Book Value while the remaining 7.1% is influenced by other variables not examined in this study.